CYTOCHEMICAL LOCALIZATION OF CATALASE IN LEAF MICROBODIES (PEROXISOMES) - Frederick, Sue Ellen (The Rockefeller University Press, 1969)
Segments of mature tobacco leaves were fixed in glutaraldehyde, incubated in medium containing 3,3'-diaminobenzidine (DAB) and hydrogen peroxide, and postfixed in osmium tetroxide. Electron microscopic observation of treated tissues revealed pronounced deposition of a highly electron-opaque material in microbodies but not in other organelles. The coarsely granular reaction product is presumably osmium black formed by reaction of oxidized DAB with osmium tetroxide. Reaction of the microbodies with DAB was completely inhibited by 0.02 M 3-amino-1,2,4-triazole and was considerably reduced by 0.01 M potassium cyanide. These results, when considered in light of recent biochemical studies, strongly suggest that catalase is responsible for the reaction. Sharp localization of this enzyme in microbodies establishes that they are identical to the catalase-rich "peroxisomes" recently isolated from leaf cell homogenates. A browning reaction that occurred in leaves during the incubation step was inhibited by cyanide but not by aminotriazole and therefore could not have been caused by the same enzyme. This reaction and a slight deposition of dense material within primary and secondary walls are ascribed to oxidation of DAB by soluble and wall-localized peroxidases.